26.4 A U.S. EXPERT CONSENSUS SURVEY ON THE USE OF LONG-ACTING INJECTABLE ANTIPSYCHOTIC DRUGS IN PATIENTS WITH SCHIZOPHRENIA, SCHIZOAFFECTIVE DISORDER AND BIPOLAR DISORDER - Sajatovic, Martha (Schizophr Bull, 2019)
BACKGROUND: A recent expert consensus survey evaluated the relative appropriateness of LAI use for a variety of patient characteristics and clinical scenarios as well as optimal prescribing practices for initiation and continuation/maintenance treatment with LAIs. The survey was administered online to experts in the United States and contained 50 questions (total of 916 response options) to elicit respondents’ opinions and practices regarding LAI prescribing for patients with schizophrenia/schizoaffective and bipolar disorders. METHODS: Aligned with the patient assessment and clinical decision-making process, the survey was organized into 3 overarching and sequential sections: (1) identifying patients, (2) initiation of therapy, and (3) maintenance treatment. Respondents rated options on relative appropriateness/importance using a 9-point scale. Consensus was determined using chi-square test of score distributions. Mean (SD) ratings were calculated. RESULTS: A total of 175 experts were invited to take the survey, 42 of whom agreed to participate (24%). Of those sent the survey, 34 experts completed it (81%). Recommendations for selection of most appropriate patients for whom LAI might be recommended aligned with research on risk factors for nonadherence and poor outcomes for patients with schizophrenia/schizoaffective or bipolar disorder. Findings suggested, contrary to general practice patterns, that LAI use may be appropriate earlier in the disease course and in younger patients. Results for bipolar disorder were similar to those for schizophrenia but with less consensus. Experts agreed that the most important LAI selection factor was patient response/tolerability with previous antipsychotics. An adequate therapeutic LAI trial was defined as the time to steady state ±1–2 injection cycles. Experts suggested that oral efficacy and tolerability be established before switching to an LAI, without consensus on the required time, and that the time for oral supplementation and next injection interval be determined by time to attainment of therapeutic LAI levels. Most experts agreed ≥1 adequate LAI trial is needed to identify antipsychotic inefficacy. Little agreement existed about switch strategies between LAIs. CONCLUSIONS: Expert guidance may aid clinicians in their decisions regarding selecting appropriate patients for LAI and initiating/maintaining LAIs in individuals with schizophrenia/schizoaffective or bipolar disorder.